Personal best : n - Fricker, Peter, 1950- 4 0 16; Brockett, Camilla; 5 Australian Institute of Sport (Camberwell, Victoria : Penguin Group (Australia), 2008)
This comprehensive guide to getting fit and staying fit comes from the Australian Institute of Sport. It shows readers how to improve their lifestyle and nutrition to ensure that their exercise program is well supported and that their new-found fitness is long-lasting. It even includes 14 tasty recipes.--Publisher.
Australian Instute of Sport;Includes index.
Keywords: 2 -- 0; 6; Physical fitness.;Exercise.; 20; 2